Use of Braile in Oral Health Education for the Visually Impaired Person - Systematic Review and Meta-Analysis - Gabriel Oliveira Figueiredo; Marcela Baraúna Magno (Portal de Periódicos da Marinha do Brasil, 2022)
Objective: To evaluate the use of Braille, alone or combined, as a method of oral health education for patients with visual impairment. Methods: A search strategy was performed in 6 databases and gray literature, and studies published until February 2021 were retrieved. Following the acronym PICOS, randomized controlled clinical trials (S) that evaluated people with visual impairment (P) who received oral hygiene instruction with educational methods containing braille alone or combined (I) compared to educational methods without Braille (C) and evaluated its influence on oral hygiene indices (O) were considered eligible. The risk of bias of studies considered eligiblew was assessed using the ROB.2 tool and meta-analyses were performed to compare the different methods in relation to plaque and gingival index. The certainty of the evidence was assessed (GRADE). Results: Nine articles were included in this review and five in the meta-analysis. All studies were classified as 'some concern' regarding the risk of bias. Braille, when used isolated, is inferior to other methods (p<0,05); when used in association with audio or audio-tactileperformance (ATP) it is similar to ATP (p>0,05), and when implemented together with ATP, it is superior to techniques without Braille (p<0,05). The certainty of the evidence ranged from very low to moderate. Conclusion: Multisensory methods including Braille and ATP are more efficient, while Braille used alone is less efficient, when both are compared to oral health education methods without Braille.